2015
DOI: 10.1021/acs.orglett.5b01803
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Catalyzed C-Arylation of Amino Acid Derived Hydantoins

Abstract: Palladium(II) trifluoroacetate (5 mol %) catalyzes the C-arylation of N,N-disubstituted hydantoins by aryl iodides in good yield. The reaction proceeds through base-promoted enolization of the amino acid derived hydantoins, and the resulting 5,5-disubstituted hydantoins may be deprotected at one or both N atoms to yield biologically active structures or alternatively hydrolyzed to the parent α-aryl α-amino acids. The reaction is successful with a variety of parent amino acids and a range of electron-rich and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Clayden et al examined α-arylations of cyclic amino acids hydantoin derivatives (61a-61c) under the Pd(TFA) 2 /L-9 catalytic system using aryl iodides (62a-62c) as aryl sources. They found α-arylated products (63a-63e) could be obtained in good yields through ZnF 2 -mediated transmetallation (Scheme 26) [77].…”
Section: Palladium-catalyzed Intramolecular α-C(sp 3 )-H Arylations Of Cyclic Carbonyl Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clayden et al examined α-arylations of cyclic amino acids hydantoin derivatives (61a-61c) under the Pd(TFA) 2 /L-9 catalytic system using aryl iodides (62a-62c) as aryl sources. They found α-arylated products (63a-63e) could be obtained in good yields through ZnF 2 -mediated transmetallation (Scheme 26) [77].…”
Section: Palladium-catalyzed Intramolecular α-C(sp 3 )-H Arylations Of Cyclic Carbonyl Compoundsmentioning
confidence: 99%
“…Clayden et al examined α -arylations of cyclic amino acids hydantoin derivatives ( 61a-61c ) under the Pd(TFA) 2 / L-9 catalytic system using aryl iodides ( 62a-62c ) as aryl sources. They found α -arylated products ( 63a-63e ) could be obtained in good yields through ZnF 2 -mediated transmetallation (Scheme 26 ) [ 77 ].
Scheme 25 α -(sp 3 )-H arylations of oxazol-5-ones by Hartwig et al
Scheme 26 α -(sp 3 )-H arylations of hydantoins reported by Claden et al
…”
Section: Transition-metal Catalyzed α -C(sp 3 )-H Arylation Of Cyclic Carbonyl Compoundsmentioning
confidence: 99%
“…Many elegant methods have been established for the stereoselective synthesis of α-substituted derivatives starting from amino acids templates. [3] Furthermore, the synthetic methods for tetrasubstituted α-aryl amino acids mainly require the use of specialized metal catalysts (usually palladium, iron, rhodium, chromium, and copper based) [4] for enol-aryl coupling reactions. Other intriguing processes are conducted in the presence of an organometallic base and involving the functionalization of an amino acid through 'selfregeneration of chirality', [5] via Sommelet-Hauser rearrangement, [6] or adopting the Kawabata's principles of "memory of chirality" (MOC).…”
Section: Introductionmentioning
confidence: 99%
“…This transformation proceeds by a concerted S N Ar mechanism, but the use of a urea tether to impose a conformational preference on the intermediate means that—unlike the classical Truce–Smiles rearrangement, which typically proceeds only with electron‐deficient aromatic rings—the electronic nature of the migrating aryl group is of little consequence to the outcome of the reaction . The N to C aryl migration that results has been developed into a versatile transition metal‐free route to a range of products including enantio‐enriched α‐quaternary amines, hydantoins, medium‐ring heterocycles, and α‐quaternary amino acids …”
Section: Introductionmentioning
confidence: 99%